The Concept of Automatic Transport System Utilizing Weight Sensor - Yurni Oktarina; Tresna Dewi; Pola Risma (Computer Engineering and Applications Journal, 2020)
The current pandemic situation insists that people find a way to create a physical distance, limiting the number of people in a closed room. The human need for commuting has led to the idea of an automatic transport system that can transport people and goods without the assistance of a driver. This idea can lead to a new "normal" and reduced cost of manufacturing in the industry. The paper discussed the concept of an automatic transport system using a weight sensor. An automatic vehicle is designed to transport loads of different packages and be allocated automatically based on the weight of the package. The system is designed to be as simple as possible to increase the scope for implementation.